Soroprevalência de leptospirose e brucelose em canis comerciais de reprodução - Bisinoto, Mariana Barbosa (2016)
Due to the lack of studies related to reproductive problems that occur with dogs, it is aimed to conduct a research in commercial kennels about the presence of diseases that do not cause apparently symptoms and go unnoticed by the owner and some professionals, causing economic losses like the loss of puppies. Among the diseases was selected Brucellosis, specifically Brucella canis, Brucella abortus and Leptospirosis which are zoonoses that has important health value. 155 animals samples were collected where kennels owners agreed to participate and take a survey on the reproductive history of each animal. It was collected approximately 7 ml of blood by puncture of the external jugular and placed in plastic microtube -20°C for later performing of the diagnostic. For the diagnosis of Leptospira spp was performed a Microscopic agglutination test (MAT) whose live antigens included: autumnalis, Australis, Bataviae, Bratslava, canicola, Copenhagini, Gryppotyphosa, serovar, hebdomadis, icterohaemorragiae, Pomona, Pyrogenes, tarassovi, Wolfi and Djasiman and considered positive samples screened blood serum at 1:100 dilution that exhibited 50% or more of agglutinated Leptospira observed in dark field microscope. For diagnostic anti-Brucella canis, antibodies immunochromatic assays were used (Alere® Kit) according to the manufacturer. To search for anti-Brucella abortus antibodies was performed as a screening test buffered plate acid (AAT), and a confirmatory test for 2- mercaptoethanol (2-ME), the result was interpreted as positive to the appearance of lumps in slow agglutination test (SAL) and 2-ME respectively. It was not found positive animals to Leptospirosis. In the AAT test, 63,3% were found positive and only three (6,7%) were confirmed in 2-ME. For Brucella canis only 9,5% were found positive. It is concluded that there are prevalence of these diseases in the kennels and is extremely important the investigation of it by the kennels owners when entering the place with animals.